2013
DOI: 10.4103/0976-9668.107268
|View full text |Cite
|
Sign up to set email alerts
|

Objective structured practical examination in biochemistry: An experience in Medical College, Kolkata

Abstract: Background:Undergraduate medical examination is undergoing extensive re evaluation with new core educational objectives being defined. Consequently, new exam systems have also been designed to test the objectives. Objective structured practical examination (OSPE) is one of them.Objectives:To introduce OSPE as a method of assessment of practical skills and learning and to determine student satisfaction regarding the OSPE. Furthermore, to explore the faculty perception of OSPE as a learning and assessment tool.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…Unlike TPE group, majority of students in TPE+OSPE and OSPE groups similar to other studies (5,7,16,21) felt that OSPE questions were more relevant, sufficient time was given to them, this assessment tool is more fair, helps to score better, less stressful and eliminates bias. These items were satisfactions criteria in feedback questionnaire.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Unlike TPE group, majority of students in TPE+OSPE and OSPE groups similar to other studies (5,7,16,21) felt that OSPE questions were more relevant, sufficient time was given to them, this assessment tool is more fair, helps to score better, less stressful and eliminates bias. These items were satisfactions criteria in feedback questionnaire.…”
Section: Discussionsupporting
confidence: 71%
“…Although, many options are available to achieve this purpose, the Objective Structured Practical Examination (OSPE) is a highly recommended method (2,(5)(6)(7)(8)(9). This assessment tool is derived from Objective Structured Clinical Examination (OSCE) by Harden and Gleeson and used for evaluation of basic sciences, preclinical and paraclinical students (6,10).…”
Section: Introductionmentioning
confidence: 99%
“…Many positive aspects of OSPE have been documented by various authors: OSPE tests the desired components of competence better and eliminates the examiner-bias prevalent in the CPE [10][11][12][13][14][15]. The examiner-bias in CPE scores is evident in this study too: Many students in India are not fluent in English, which is the medium of education, and therefore, even a knowledgeable student is often unable to reply satisfactorily to the examiner's queries.…”
Section: Discussionmentioning
confidence: 99%
“…The OSPE evaluates a range of competencies [7,8], measures practical psychomotor skills, eliminates subjectivity [7,9] and examiner bias [8,10], reduces total time for practical examination, enables uniformity in student assessment, decreases stress levels among students [11], has a wider discrimination index and high reliability [12] and helps students to grasp various components of competencies and also obtain feedback [11,13]. A Hyderabad-based study [14] has reported use of Computer-assisted OSPE (COSPE) in the subject of Anatomy, wherein, the OSPE questions were formulated using well-labelled specimens, animated and projected as a PowerPoint presentation on an LCD screen.…”
Section: Introductionmentioning
confidence: 99%